SERVICE QUALITY, STORE ATMOSPHERE, AND PRODUCT VARIETY ON CONSUMER PURCHASE DECISIONS AT TOKO SEMBAKO BU SRIYU KEDIRI - Maqoyyim Husna; Anita Sumelvia Dewi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This research investigates how service quality, store atmosphere, and product variety affect customer purchase choices at Toko Sembako Bu Sriyu in Kediri City. A quantitative approach was adopted, gathering data through surveys from 200 previous store customers selected via purposive sampling. Multiple linear regression analysis in SPSS was applied to the data. The partial analysis (t-test) revealed that neither service quality nor store atmosphere significantly impacts purchasing decisions. In contrast, product variety demonstrated a positive and significant effect. Simultaneous testing (F-test) confirmed that, taken together, all three variables significantly influence purchase decisions. Nevertheless, the model's explanatory power is limited, as shown by a low R² value of 0.043, implying that factors outside this study account for most of the variance in consumer decisions. This analysis confirms that product variety is the key factor driving purchasing behavior among grocery store consumers. This study intends to contribute practical knowledge to retail marketing management literature and to provide actionable guidance for grocery retailers seeking to refine their marketing strategies.